Perencanaan Investasi Pembangunan Perumahan Di Desa Pilangsari Kecamatan Ngrampal Kabupaten Sragen - Fadlurrahman, Azhar, Ir. H. Muhammad Nur Sahid, M.M., M.T (2016)
The counstruction of housing has grown very much rapidly in Sragen Regency. Especially in the Pilangsari Village, Ngrampal Region. This also caused by one of the factor economic.Invest the property of giving an important for economic growth. The study is done in the Region of Ngrampal in a vacant land as an object research have broad 3685 m2. This research discuss how to determine whether or not investing in property. In this research with 4 the stage, the first phase do the spread of the questionnaire and data collection, next in stage 2 process data who has been collected to processed using SPSS application, then stage 3 discuss the determination of investment plan and do analysis of economic feasibility which includes a method of calculation payback period (PP), return of investment (ROI), net present value (NPV), internal rate of return (IRR), break event point (BEP), indeks profitability (IP), benefit cost ratio (BCR). And the final stage is looking for conclusions obtained PP value in return on investment in fixed cash flow values obtained 22 month 23 days, while the return on investment cash flow was still obtained value of 23 months and 10 days. ROI before taxes worth 4,39% per month = 52,67 % per year, ROI after tax value worth 3,95 % per month or 47,40% per year. NPV is positive RP 549.951.150,80; IRR = 14,17% > interest rate of 10%; BCR = 1,037 > 1, the IP = 1,037 > 1, and BEP reached 19 units housing. Thus capable of being known, through various planning phase of the development of a housing complex investment in the Pilangsari Village, Ngrampal Area, Sragen Regency can be implemented.